On the Size and g-factor of Uniform Star Polymers in a Dilute Solution: A Monte Carlo Simulation - Siripon Anantawaraskul; Nutshera Kitthitanesuan (Agriculture and Natural Resources, 2009)
The size of uniform star polymers in a dilute solution was investigated using Monte Carlo simulation and a self-avoiding walk (SAW) model with the pivot algorithm. Chain conformations were simulated in a 3D cubic lattice. The size of these polymer chains, reflected through the mean square radius of gyration (<Rg2>), was examined and compared with that of linear analog chains. The results showed that star polymers have a smaller size compared to linear chains with the same total number of segments. The radius of gyration increased with the total number of segments, but it decreased with an increase in the number of arms. This indicated that the segment-repelling effect due to the “excluded volume” had a smaller influence when compared to the effect of the molecular structure restriction. Simulated g-factor values were compared with various theoretical predictions and agreed well, even with a Zimm-Stockmayer prediction for ideal chains with no excluded volume effect. This indicated that the solvent practically had no effect on the relative size compared to the linear analog and that the g-factor of ideal chains could be used as a good estimator for the g-factor of real chains in a dilute solution.